2017
DOI: 10.1017/s0007114517000447
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adolescents’ glycaemic and insulinaemic responses to high and low glycaemic index breakfasts: a randomised control trial

Abstract: During puberty young people undergo significant hormonal changes which affect metabolism and, subsequently, health. Evidence suggests there is a period of transient pubertal insulin resistance, with this effect greater in girls than boys. However, the response to everyday high and low glycaemic index (GI) meals remains unknown. Following ethical approval, forty adolescents consumed a high GI or low GI breakfast, in a randomised cross-over design. Capillary blood samples were taken during a 2-h postprandial per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…Finally, in the present study plasma insulin concentrations were consistently higher in girls than boys, yet the response to exercise did not differ between the sexes. The finding that girls exhibit greater insulin resistance during adolescence is consistent with previous research whereby the insulinaemic response to a mixed meal was 30-40% higher in girls than boys [15]. The present study aimed to examine whether HIIE could reduce the postprandial differences in insulin sensitivity observed between the sexes and attenuate the insulin resistance observed in adolescent girls.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, in the present study plasma insulin concentrations were consistently higher in girls than boys, yet the response to exercise did not differ between the sexes. The finding that girls exhibit greater insulin resistance during adolescence is consistent with previous research whereby the insulinaemic response to a mixed meal was 30-40% higher in girls than boys [15]. The present study aimed to examine whether HIIE could reduce the postprandial differences in insulin sensitivity observed between the sexes and attenuate the insulin resistance observed in adolescent girls.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, throughout adolescence, differences in insulin sensitivity exist between the sexes, with the postprandial peak in insulin following a standardised mixed meal being 30-40% greater in adolescent girls (for peak plasma insulin concentrations) when compared with adolescent boys [15]. Yet, there has been no research to date to ascertain whether the sex differences in the postprandial insulin resistance persist following an acute bout of exercise and should exercise reduce the postprandial response, whether exercise can be used as a potential intervention to reduce insulin resistance in adolescent girls.…”
Section: Introductionmentioning
confidence: 99%
“…There continues to be a considerable gap in knowledge on the complex interplay of hormones, genes, lifestyle and environment that might contribute to the sex differences in rates of youth‐onset type 2 diabetes, and why this trend reverses in adulthood. Insulin resistance during puberty can be as much as 30% greater in girls compared to boys and a recent study by Cooper et al showed that pubertal females have a 30 to 40% higher insulinaemic response to a high glycemic index meal compared to pubertal males . These sex differences may partly be explained by higher adiposity in pubertal females vs males .…”
Section: Discussionmentioning
confidence: 99%
“…The present study extends this relationship to a sample of adolescent boys and girls, in response to an ecologically valid mixed meal. Although the meals provided between the present study and previous work (11) were different, they offered the same relative energy provision (1•5 g/kg body mass of carbohydrate). Collectively, these results suggest that basal metabolic function is important for determining the physiological response to test meals.…”
Section: Discussionmentioning
confidence: 99%
“…This can be assessed in various ways (such as waist circumference, sum of skinfolds and BMI) and is considered an important risk factors for the development of insulin resistance and, subsequently, type 2 diabetes (2,9,10) . Sex and pubertal status are also other risk factors during childhood (up to 11 years old) and adolescence (11-18 years old), given that there is a degree of pubertal insulin resistance, which may be of greater magnitude in females (11)(12)(13) ; thus, it is particularly important to understand the association between risk factors of insulin resistance during adolescence, which has not been explored to date. Low physical activity and physical fitness are risk factors for the development of type 2 diabetes (14) in adults and are also linked with poor cardiometabolic health in children and adolescents (15) .…”
mentioning
confidence: 99%